KOMPARASI USAHA PEMBESARAN IKAN NILA DI KOLAM TANAH DAN KERAMBA JARING APUNG PADA KOLONG - Emia Pepayocha; Ardiansyah Kurniawan; Endang Bidayani (Jurusan Akuakultur, Universitas Bangka Belitung, 2022)
Communities on the island of Bangka use soil ponds and floating net cages on ex tin mines lake for tilapia cultivation. Currently, the comparison of the productivity of the two cultivation system for Tilapia cultivation is not known. This study analyzed the business and productivity of tilapia rearing under floating net cages and soil ponds in Air Mesu Village, Pangkalan Baru District, Central Regency. The method used in this study is a survey method with case study techniques with data collection through interviews, questionnaires, and observations. Overall, the business of rearing Tilapia with the KJA system and soil ponds in Air Mesu Village is feasible to develop because the R/C ratio is >1. The use of the KJA system has an R/C ratio and greater productivity than the ground pool. Yield productivity of 25.12 kg/m2 in the KJA system and 19.52/m2 in the soil pond system.